2014
DOI: 10.20527/bipf.v2i2.848
|View full text |Cite
|
Sign up to set email alerts
|

Meningkatkan Hard Skills Dan Soft Skills Siswa Melalui Model Pembelajaran Koooperatif Tipe STAD

Abstract: Penelitian ini secara umum bertujuan untuk mendeskripsikan keefektifan model pembelajaran kooperatif tipe STAD dalam meningkatkan hard skills dan soft skills  siswa SMAN 8 Barabai pada pokok bahasan fluida statis. Secara khusus untuk mendeskripsikan keterlaksanaan RPP model kooperatif tipe STAD,  hard skills siswa, soft skills siswa dan respon siswa. Metode penelitian yang digunakan merupakan penelitian tindakan kelas model Kemmis dan Mc Taggart. Hasil penelitian menunjukkan bahwa terjadi peningkatan hard skil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Infrastructure is the most important thing in supporting learning so that learning is maximized which is supporting facilities. This is in line with the meaning of facilities and infrastructure in the monograph on Islamic education management, infrastructure is a facility provided to an institution in the form of physical and intuitive human resources providing education (Alfiansyah, Muhammad 2014).…”
Section: Duplicating Factorssupporting
confidence: 60%
“…Infrastructure is the most important thing in supporting learning so that learning is maximized which is supporting facilities. This is in line with the meaning of facilities and infrastructure in the monograph on Islamic education management, infrastructure is a facility provided to an institution in the form of physical and intuitive human resources providing education (Alfiansyah, Muhammad 2014).…”
Section: Duplicating Factorssupporting
confidence: 60%
“…Core Competencies are translations or operationalization of Standar Kompetensi Lulusan (SKL, Graduate Competence Standard) in the form of qualities that must be possessed by those who have completed education at a certain education or certain level of education, an overview of the main competencies grouped into aspects of attitudes, knowledge and skills (affective, cognitive and psychomotor) that must be learned students for a school level, class and subject (Mubarok, 2019;Haristo Rahman et al, 2020). Core competencies must describe the quality that is balanced between the achievement of hard skills and soft kills (Alfiansyah et al, 2014).…”
Section: Sejarah Kebudyaan Islam/history Of Islamic Culturementioning
confidence: 99%
“…From various definitions above, it can be concluded that soft skills are students' ability to communicate verbally and in writing, supported by high confidence and good self-management so that students can put themselves in a social and organizational environment. Hard Skills, (Alfiansyah et al 2014) states that hard skills are the basis of analytical footing or a decision related to enrichment theory. Delita et al (2016) states that hard skills are the skills of the learning process whose results can be seen immediately.…”
Section: Introductionmentioning
confidence: 99%